Bimbingan Kelompok Teknik Diskusi Buzz Group untuk Meningkatkan Kemampuan Mengemukakan Pendapat - Eva Fitriyani; Sri Wiyanti; Ulya Makhmudah (Universitas Sebelas Maret, 2022)
Abstract: The purpose of this study was to determine the effectiveness of the group guidance of the buzz group discussion technique to improve the ability to express opinions. This research is experimental research with Quasi-Experimental Design. Students as research subjects who can express low opinions obtained from the pretest results. The research subjects were divided into two groups, namely the experimental group and the control group. The experimental group was given treatment in the form of group guidance on buzz group discussion techniques to improve the ability to express opinions, and the control group was not given treatment. The analysis used the MannWhitney technique obtained Z of -4,984 with p value 0,000 (0,000 <0,05), meaning that there is a difference in the results of the experimental group with the control group, which shows an increase in the score in the experimental group after being given treatment. In addition, the Wilcoxon technical analysis showed Z of -3,624 with a significance value of 0,000, then 0,000 <0,05, meaning that there was an increase in the posttest score in the experimental group after being given treatment in the form of group guidance on the buzz group discussion technique. Based on the analysis results, it was concluded that the group guidance of the buzz group discussion technique effectively improved the ability to express opinions.Abstrak: Tujuan penelitian ini adalah untuk mengetahui keefektifan bimbingan kelompok teknik diskusi buzz group untuk meningkatkan kemampuan mengemukakan pendapat. Penelitian ini merupakan penelitian eksperimen dengan Quasi Experimental Design. Peserta didik sebagai subjek penelitian yang memiliki kemampuan mengemukakan pendapat rendah, diperoleh dari hasil pretest. Subjek penelitian dibagi menjadi 2 kelompok yaitu kelompok eksperimen dan kelompok kontrol. Treatment berupa bimbingan kelompok teknik diskusi buzz group untuk meningkatkan kemampuan mengemukakan pendapat diberikan kepada kelompok eksperimen, kelompok kontrol tidak diberi treatment. Analisis yang digunakan teknik Mann Whitney diperoleh Z sebesar -4,984 dengan nilai signifikansi sebesar 0,000, maka 0,000 < 0,05, artinya ada perbedaan hasil kelompok eksperimen dengan kelompok kontrol yang menunjukkan ada peningkatan skor pada kelompok eksperimen setelah diberi treatment. Selain itu analisis teknik Wilcoxon yang menunjukkan Z sebesar -3,624 dengan nilai signifikansi 0,000, maka 0,000 < 0,05 artinya ada peningkatan skor posttest pada kelompok eksperimen setelah diberi treatment berupa bimbingan kelompok teknik diskusi buzz group. Berdasarkan hasil analisis diperoleh simpulan bahwa bimbingan kelompok teknik diskusi buzz group efektif untuk meningkatkan kemampuan mengemukakan pendapat.